(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The usefulness of RBIA in improving organisational decision-making and operational efficiency is examined in this study. Traditional compliance-focused audits have not been able to adequately detect new risks and guide strategic decisions in today’s complex and changing corporate environment.